Problematic anger among military personnel after combat deployment: prevalence and risk factors - Andreas Espetvedt Nordstrand; Frederick Anyan; Hans Jakob Bøe; Odin Hjemdal; Laura Katherine Noll; Jon Gerhard Reichelt; David Forbes; Amy B. Adler (BMC Psychology, 2024)
Abstract Background Problematic anger, characterized by excessive frequency, intensity, and duration of anger which causes substantial emotional distress and functional interference, poses a marked challenge in military populations. Despite its importance, research on this topic is limited. This study contributes to the literature by exploring problematic anger in a large sample of Norwegian military personnel who served in NATO missions in Afghanistan. Methods All Norwegian military personnel who deployed to Afghanistan between 2001 and 2020 were sent a link to a cross-sectional web-based survey by the Joint Medical Services of the Norwegian Armed Forces in 2020. A total of 6205 individuals (response rate: 67.7%) participated. The cross-sectional survey assessed problematic anger, mental and physical health, war zone stressor exposure, and quality of life. Results Overall, 8.4% of participants reported problematic anger. Mental health disorders, deployment-related shame and guilt, chronic pain, and challenges with the military-to-civilian transition were independently associated with problematic anger. Both staying in service and maintaining a part-time connection with the military as a reservist mitigated the risk of problematic anger after deployment, compared to complete separation from military service. Conclusion Findings demonstrate a sizeable prevalence of problematic anger among veterans of combat deployments. Given the associations between problematic anger and mental health disorders, chronic pain, and transition challenges, interventions designed to mitigate problematic anger need to be multi-faceted, including the possibility of maintaining an ongoing connection to military service. By reducing the risk of problematic anger, occupational, interpersonal and health outcomes may be improved for service members. Future research should examine the impact of problematic anger on adjustment over time, prevention strategies, and problematic anger in other high-risk occupations.